2016
DOI: 10.1016/j.cognition.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving the agency of harmful agents: A test of dehumanization versus moral typecasting accounts

Abstract: It is clear that harmful agents are targets of severe condemnation, but it is much less clear how perceivers conceptualize the agency of harmful agents. The current studies tested two competing predictions made by moral typecasting theory and the dehumanization literature. Across six studies, harmful agents were perceived to possess less agency than neutral (non-offending) and benevolent agents, consistent with a dehumanization perspective but inconsistent with the assumptions of moral typecasting theory. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 52 publications
11
45
1
Order By: Relevance
“…We find that while heroes can be lauded for having admirable agentic traits, they are simultaneously seen as having less of a "mind" in terms of their ability to feel. This contrasts other work suggesting that people simply assign more of a mind and various positive traits to those who are seen favorably and less mind in general to those who are disliked (Heflick et al, 2011;Khamitov et al, 2016). Similarly, veterans were seen as higher on both dimensions of social perception (agency and communion), which both predicted morality, and neither predicted either form of dehumanization.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…We find that while heroes can be lauded for having admirable agentic traits, they are simultaneously seen as having less of a "mind" in terms of their ability to feel. This contrasts other work suggesting that people simply assign more of a mind and various positive traits to those who are seen favorably and less mind in general to those who are disliked (Heflick et al, 2011;Khamitov et al, 2016). Similarly, veterans were seen as higher on both dimensions of social perception (agency and communion), which both predicted morality, and neither predicted either form of dehumanization.…”
Section: Discussioncontrasting
confidence: 87%
“…Despite (or perhaps even because of) the fact that we hold veterans in high esteem as heroic moral agents, moral typecasting predicts that people are likely to see veterans as capable of thinking but also as relatively unfeeling, emotionally unresponsive, and uncommunicative. This is another important test of the unique value of moral typecasting and mind perception, as other theories would instead predict that lauded groups are humanized on all dimensions, and disliked groups or objectified groups are dehumanized on all dimensions (Heflick, Goldenberg, Cooper, & Puvia, 2011;Khamitov et al, 2016).…”
Section: Moral Typecasting Of Veterans Its Consequencesmentioning
confidence: 99%
“…Indeed, nonhuman animals, robots, and objects are seldom the subjects of moral blame. While some work indicates that people dehumanize those deserving of punishment (Khamitov et al, 2016), recent evidence suggests that morally motivated perpetrators may also humanize others to justify aggression against them (Rai et al, 2017); a proposition consistent with earlier research showing that dehumanization renders people less susceptible to moral blame (Bastian et al, 2011). More-ideally experimen-tal-work is necessary to understand how political dehumanization relates to moral (or affective) polarization and behavioural expressions of out-party hostility.…”
Section: Discussionmentioning
confidence: 65%
“…To manipulate dehumanization, we drew on previous research that identified personality traits that are seen as highly humanizing, but which are counterbalanced for positive and negative valence. Specifically, in the humanized condition, the stranger was described as a 29-year-old man with brown hair and brown eyes named John, who is "ambitious and imaginative, but also high-strung and insecure", whereas in the dehumanized condition, the stranger was simply described as a "man" (48,49). Participants then rated their willingness to break the stranger's thumb and assessed the stranger's mental states.…”
Section: Methodsmentioning
confidence: 99%